Teenagers' Views on the Agricultural Sector in Anjir Muara Kota Village - Ahmad Husaini; Mutiani Mutiani; Rusmaniah Rusmaniah; Sigit Triyono; Sovia Husni Rahmia (Journal of Social Development, 2026)
The main issue in this study is the low interest of teenagers in the agricultural sector in Anjir Muara Kota Village. This condition has implications for the obstruction of farmer regeneration and potential threats to future food security. The purpose of this study is to identify the views of teenagers in Anjir Muara Kota Village towards the agricultural sector, where interest among teenagers in engaging in agriculture is declining. This study uses a qualitative approach with a descriptive method. The research data consists of primary and secondary data, obtained through information gathering techniques such as observation, interviews, and literature studies. This study shows that the low interest of adolescents in the agricultural sector is influenced by economic, social, and technological factors, as well as a lack of environmental support. Adolescents consider agriculture to be financially unpromising, physically demanding, and low in prestige. Further research is recommended to explore a wider area and assess the role of education and technology in shaping adolescents' interest in agriculture.